2018
DOI: 10.1155/2018/6157249
|View full text |Cite
|
Sign up to set email alerts
|

Supervised Learning for Suicidal Ideation Detection in Online User Content

Abstract: Early detection and treatment are regarded as the most effective ways to prevent suicidal ideation and potential suicide attempts—two critical risk factors resulting in successful suicides. Online communication channels are becoming a new way for people to express their suicidal tendencies. This paper presents an approach to understand suicidal ideation through online user-generated content with the goal of early detection via supervised learning. Analysing users’ language preferences and topic descriptions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
109
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(134 citation statements)
references
References 35 publications
1
109
0
4
Order By: Relevance
“…Our results show that the proposed combined neural network model performs better in comparison to single LSTM and CNN classifiers. Concerning the accuracy performance, our results outperform the accuracy of the experiment previously applied on the same dataset [31].…”
Section: Classification Analysis Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…Our results show that the proposed combined neural network model performs better in comparison to single LSTM and CNN classifiers. Concerning the accuracy performance, our results outperform the accuracy of the experiment previously applied on the same dataset [31].…”
Section: Classification Analysis Resultsmentioning
confidence: 46%
“…Sawhney et al [30] work revealed the strength and ability of C-LSTM-based models as compared to other deep learning and machine learning classifiers for suicide ideation recognition. Ji et al [31] compared the LSTM classifier with five other machine learning models and demonstrated the feasibility and practicability of the approaches. His study provides one of the major benchmarks for the detection of suicide ideation on Reddit SuicideWatch and Twitter.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This baseline is a rule-based model for classifying a user based on a strict and soft match criteria according to presence of a concept in the user's content and the suicide risk severity lexicon. For a competitive baseline, we compared this baseline with word-embedding and TF-IDF based approaches for suicide classification [29]. As we also experimented with word-embedding models trained over suicide and non-suicide related content, using compositions of word vectors [3,32,41], the baseline based on suicide risk severity lexicon outperformed these competitive approaches.…”
Section: Baselinesmentioning
confidence: 99%
“…30 Ji et al found comparable results, demonstrating that machine learning techniques could leverage statistical, linguistic, word embedding and topic features to achieve 90% accuracy in identifying suicide ideation on Reddit and Twitter. 31 Despite these promising results, the utility of identifying suicidal ideation may be limited due to low positive predictive value and modest sensitivity for suicide attempts. This is due to the low incidence of suicide attempts when compared with incidence of suicidal ideation.…”
Section: Ai-driven Prediction Relating To Suicide Risk Factors Suicidmentioning
confidence: 99%